Analysis of Frequency and Intensity Levels of Sound Waves in the Bedana Traditional Dance Music of Lampung Using an Ethnoscience Approach - Anggraini, Welly; Kamil, Badrul; Masya, Hardiyansyah; Sari, Indah (Jurnal Pijar Mipa, 2025)
This study analyzes the frequency and intensity levels of sound waves produced by musical instruments in the Bedana traditional dance of Lampung. An ethnoscience approach is employed, integrating cultural and scientific perspectives to examine sound phenomena in the local context. Data were gathered through sound frequency and intensity measurements using advanced audio analysis software, complemented by qualitative cultural observations. The results reveal distinct frequency variations among instruments, contributing to the dance’s harmonic expression. Notably, statistical tests indicate significance, reinforcing the hypothesis regarding the unique acoustic properties of each instrument. This research underscores the importance of ethnoscience in cultural conservation and traditional arts education, offering insights for future ethnomusicological studies and cultural preservation initiatives.